THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY AND OWNERSHIP STRUCTURE ON PROFITABILITY - Carolyn, Helen; Fauzi, Achmad; Utaminingtyas, Tri Hesti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
The purpose of this study is to determine the effect of Corporate Social Responsibility (CSR) and Ownership Structure proxied by Institutional Ownership on the profitability (ROA) of banks listed on the Indonesia StockExchange (IDX) for the period 2018-2020. The data used in this study are secondary data which is the annual reports of banks and obtained from the bank's official website and Indonesia Stock Exchange (IDX). The form of data used in this study is panel data, a combination of time-series and crosssectional data which is then processed using E-views 9 with multiple regression methods. The population is all banks listed on the Indonesia Stock Exchange (IDX) from the 2018-2020 periode, totaling 47 banks. This research used purpossive sampling with 39 banks as finale sample. The results of the study conclude that the Corporate Social Responsibility (CSR) as variable X1 has no effect on ROA and Institutional Ownership has a significantly negative effect on ROA and through the F test conducted, the two variables X (CSR and Institutional Ownership) are stated simultaneously affect ROA with a coefficient level determination of 59.87%.